On the Right to the University in Urban Capitalism - Sanjay Jolly (Media Theory)
This manifesto examines the integration of the US university into processes of urban capitalism and argues its administrative and ideological functions are critical to maintaining urban hegemony. Using the relationship between the University of Pennsylvania and the City of Philadelphia as an exemplar, I base my analysis upon three bodies of empirical evidence: the interlocking directorates of university regents; publicly available urban planning reports; and newspaper coverage of development in Philadelphia. I show that the university is essential to a social process that has as its aim the erasure – both physical and symbolic – of Black and Brown bodies from urban space. In addition to its role in the bureaucracies of urban power, the university is central within strategic narratives that mythologize the white savior and legitimize crude forms of capital accumulation. Finally, I explore the university as a site for counterhegemonic urban practice, calling on academics to integrate the notion of the Right to the University with the politics of the Right to the City.